Root functioning, tree water use and hydraulic redistribution in Quercus suber trees: A modeling approach based on root sap flow - David, Teresa S.; Pinto, Clara A.; Nadezhdina, Nadezhda; Kurz-Besson, Cathy; Henriques, Manuel O.; Quilhó, Teresa; Čermák, Jan; Chaves, M. Manuela; Pereira, João S.; David, Jorge S. (Forest Ecology and Management, 2013)
Mediterranean evergreen oaks have to survive a long summer drought. Roots may play a relevant role under these conditions. We studied their structure and function in a mature Quercus suber L. tree in central Portugal. The root system was mapped till the lowest water table level (4.5 m depth). Xylem anatomy was analyzed in a vertical profile belowground. Sap flow was continuously monitored for 1.5 yrs in the stem and roots of this intensively studied tree (heat field deformation method) and in the stem of four trees (Granier method), in relation to environmental variables and predawn leaf water potential. The sources of water uptake were assessed by stable isotope analyses in summer. Results showed a dimorphic root system with a network of superficial roots linked to sinker roots, and a taproot diverting into tangles of deep fine roots submerged for long periods, with parenchyma aerenchyma. Transpiration was not restricted in summer due to root access to groundwater. The isotopic δ18O signature of twig xylem water was similar to that of groundwater in the dry season. Two functional types of superficial roots were identified: shallow connected and deep connected roots. A modeling approach was built considering that each superficial root was linked to a sinker, with part of the root deep connected (between the stem and the sinker) and part shallow connected (between the sinker and topsoil). This conceptual framework simulated tree stem sap flow from root sap flow with a high efficiency (R2 = 0.85) in four plot trees. On an annual basis, soil water and groundwater contributions were 69.5% and 30.5% of stem flow, respectively. Annual hydraulic lift and hydraulic descent were 0.9% and 37.0% of stem flow, respectively. The trees maximize the exploitation of the environmental resources by using the topsoil water during most of the year, and groundwater together with hydraulic lift (nutrient supply) in the dry summer. This study shows that a dimorphic root system, with roots reaching groundwater, is an efficient strategy of Q. suber trees to cope with seasonal drought. Knowledge of the functional behavior of Q. suber trees under shallow water table conditions may contribute to the definition of better adapted management practices and to anticipate their responses to climate change.
Keywords: Drought; groundwater; soil water; Stable isotopes; xylem anatomy

The influence of precipitation pulses on soil respiration – Assessing the “Birch effect” by stable carbon isotopes - Unger, Stephan; Máguas, Cristina; Pereira, João S.; David, Teresa S.; Werner, Christiane (Soil Biology and Biochemistry, 2010)
Sudden pulse-like events of rapidly increasing CO2-efﬂux occur in soils under seasonally dry climates in response to rewetting after drought. These occurrences, termed “Birch effect”, can have a marked inﬂuence on the ecosystem carbon balance. Current hypotheses indicate that the “Birch” pulse is caused by rapidly increased respiration and mineralization rates in response to changing moisture conditions but the underlying mechanisms are still unclear. Here, we present data from an experimental ﬁeld study using straight-forward stable isotope methodology to gather new insights into the processes induced by rewetting of dried soils and evaluate current hypotheses for the “Birch“-CO2-pulse. Two irrigation experiments were conducted on bare soil, root-free soil and intact vegetation during May and August 2005 in a semi-arid Mediterranean holm oak forest in southern Portugal. We continuously monitored CO2-ﬂuxes along with their isotopic compositions before, during and after the irrigation. d 13 C signatures of the ﬁrst CO2-efﬂux burst, occurring immediately after rewetting, ﬁt the hypothesis that the “Birch” pulse is caused by the rapid mineralization of either dead microbial biomass or osmoregulatory substances released by soil microorganisms in response to hypo-osmotic stress in order to avoid cell lyses. The response of soil CO2-efﬂux to rewetting was smaller under mild (May) than under severe drought (August) and isotopic compositions indicated a larger contribution of anaplerotic carbon uptake with increasing soil desiccation. Both length and severity of drought periods probably play a key role for the microbial response to the rewetting of soils and thus for ecosystem carbon sequestration.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: Birch effect; d13C; Irrigation experiment; Mediterranean woodland; Soil respiration; Stable isotopes